2007
DOI: 10.2166/hydro.2007.027
|View full text |Cite
|
Sign up to set email alerts
|

Flood forecasting using support vector machines

Abstract: This paper describes an application of SVM over the Bird Creek catchment and addresses some important issues in developing and applying SVM in flood forecasting. It has been found that, like artificial neural network models, SVM also suffers from over-fitting and under-fitting problems and the over-fitting is more damaging than under-fitting. This paper illustrates that an optimum selection among a large number of various input combinations and parameters is a real challenge for any modellers in using SVMs. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(68 citation statements)
references
References 15 publications
2
65
0
1
Order By: Relevance
“…Because of the choices made by the developers of physically oriented models, each is good at simulating different parts of the hydrological cycle. In addition, the subjective choices made in soft computing approaches can result in models that perform well at different times (Han et al, 2007). By combining predictions from different models and from different modelling approaches, it is possible to take advantage of the expertise of each of them, theoretically resulting in better overall predictive capabilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the choices made by the developers of physically oriented models, each is good at simulating different parts of the hydrological cycle. In addition, the subjective choices made in soft computing approaches can result in models that perform well at different times (Han et al, 2007). By combining predictions from different models and from different modelling approaches, it is possible to take advantage of the expertise of each of them, theoretically resulting in better overall predictive capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Behzad et al (2009) reported that SVMs are able to generalize better than ANNs, though there is still some danger of under-or overfitting to the training data (Han et al, 2007) (true to some extent of virtually any model). The SVMs are also able to learn from a much smaller training set than ANNs, and the global minimum of the linear optimization is easily obtainable, whereas there is a risk of becoming trapped in a local minimum of the non-linear ANN objective function (Behzad et al, 2009).…”
Section: Approaches To Hydrological Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Current LULC maps were created using remote sensing data (Landsat 8 from May and October, sentinel 1 from November and Advanced Land Observing Satellite 2 acquired in November 2014), and image fusion techniques; the classification was done using Support Vector Machine classifier (SVMC) using ENVI version 5.2. SVMC is a non-parametric classifier, which includes a set of related learning algorithms that are used for classification and regression (Han, Chan, & Zhu , 2007) (see appendix C). The goal of image fusion techniques is to improve the spatial resolution, geometric precision and classification accuracy.…”
Section: Data and Knowledge Inputmentioning
confidence: 99%
“…Image fusion techniques and the classification based to Support Vector Machine classifier (SVMC) using ENVI version 5.2. SVMC is a non-parametric classifier, which includes a set of related learning algorithms that are used for classification and regression (Han et al, 2007). Kappa statistics and overall accuracy assessment was applied to compare the accuracy of classified data.…”
Section: Image Classificationmentioning
confidence: 99%